AIDA-CMK : multi-algorithm optimization kernel applied to analog IC sizing /: multi-algorithm optimization kernel applied to analog IC sizing. ([2015]) - Lourenço, Ricardo; Lourenço, Nuno; Horta, Nuno C. G
No abstract available